Psychological distress among medical undergraduate students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (Elsevier, 2014)
Background and Aims: It is well known that medical students are subjected to different levels of stressors during various stages of their study. Exposure to severe and prolonged stressors may cause serious psychological distress that may hinder students’ academic performance and may affect their mental and physical health as well. Therefore, this study aimed to determine the prevalence of psychological distress among medical undergraduate students throughout the different stages of their study. Methods: A sample of 551 undergraduate medical students from Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia participated in this study (First year 141, Second 119, Third 109, Fourth 101, Fifth 81), the psychological distress was assessed using the 12-item General Health Questionnaire (GHQ-12), which is the short version developed by David Goldberg and Paul Williams. A binary scoring method was used to evaluate responses (i.e. 0-0-1-1). The rate was compared between different stages of the academic programme. Results: The overall prevalence of psychological distress among medical students was found to be 31.2% and the rate was higher during clinical than preclinical phases (33.7% and 28.5% respectively). Gender wise, it was found that the rate of psychological distress was significantly higher among female (35.5%) than male students (24.3%). Conclusions: Psychological distress is common among medical students, it is higher among female than male students, and the rate is higher during clinical phase than preclinical phase.